2012
DOI: 10.1016/j.ceca.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trpc channels, Stim1 and Orai1 in PGF2α-induced calcium signaling in NRK fibroblasts

Abstract: Normal rat kidney (NRK) fibroblasts exhibit growth-dependent changes in electrophysiological properties and intracellular calcium dynamics. The transition from a quiescent state to a density-arrested state results in altered calcium entry characteristics. This coincides with modulation of the expression of the genes encoding the calcium channels Trpc1, Trpc6 and Orai1, and of the intracellular calcium sensor Stim1. In the present study we have used gene selective short hairpin (sh) RNAs against these various g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…59 Nonselective blockers SKF96365, Gd 3+ , and 2-APB were also used to further validate the implication of TRP channels. Recently, the presence of TRPC channels has been depicted in a normal rat kidney fibroblasts cell line and found to control the process of receptor-operated Ca 2+ influx 46,47 ; additionally, TRPC3 was present in the rat kidney and played a key role in the influx of Ca 2+ into principal cells of the collecting duct. 48,[52][53][54] However, the role of such channels in freshly isolated adult renal fibroblasts under native physiologic conditions remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Nonselective blockers SKF96365, Gd 3+ , and 2-APB were also used to further validate the implication of TRP channels. Recently, the presence of TRPC channels has been depicted in a normal rat kidney fibroblasts cell line and found to control the process of receptor-operated Ca 2+ influx 46,47 ; additionally, TRPC3 was present in the rat kidney and played a key role in the influx of Ca 2+ into principal cells of the collecting duct. 48,[52][53][54] However, the role of such channels in freshly isolated adult renal fibroblasts under native physiologic conditions remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…43 More recently, TRPC3 has been found in human cardiac fibroblasts and regulated cell proliferation and differentiation in atrial fibrillation. 44,45 Few other studies reported the presence of TRPC channels in normal rat kidney cell lines 46,47 and identified their localization in the adult rat and human kidney. [48][49][50][51] TRPC3 is also responsible for transepithelial Ca 2+ flux in principal cells of the renal collecting duct [52][53][54] ; however, a clear functional in vivo role of such channels remains totally unclear, especially in the diseased kidney.…”
mentioning
confidence: 99%
“…Intriguingly, several reports revealed that knocking down Orai1 suppressed SOCE despite the presence of endogenous or heterologously expressed STIM1 and TRPC1. STIM1, Orai1 and TRPC1 were found to associate into a heteromeric supermolecular complex in response to ER Ca 2+ depletion in many different cell types, including in human salivary gland (HSG) cell [102], human platelets [103], human liver cells [104], mouse pulmonary arterial smooth muscle cells [105], human parathyroid cells [106], and rat kidney fibroblasts [107]. Several models have been proposed to interpret this interaction [90,99,108,109].…”
Section: Transient Receptor Potential Canonical Channels: Additionmentioning
confidence: 99%
“…Additional evidence indicate that Ca 2+ influx is also linked to activation of other emetogenic receptors including SP tachykinin NK 1 (Lallemend et al, 2003;Lin et al, 2005;Miyano et al, 2010;Suzuki et al, 2010), dopamine D 2 (Aman et al, 2007;Wu et al, 2006), cholinergic M 1 (Oliveir and Correia-de-Sa, 2005;Sculptoreano et al, 2001), and histaminergic H 1 (Barajas et al, 2008) receptors. Moreover, other emetogens such as prostaglandins (Almirza et al, 2012;Rodríguez-Lagunas et al, 2010), cisplatin (Günes et al, 2009;Splettstoesser et al, 2007), rotavirus NSP4 protein (Hagbom et al, 2012;Hyser et al, 2010) and bacterial toxins (Poppoff and Poulain, 2010;Timar Peregrin et al, 1999) have the ability to induce extracellular Ca 2+ influx through Ca 2+ channels present in the cell membrane.…”
Section: Introductionmentioning
confidence: 99%